1991
DOI: 10.1007/bf01887344
|View full text |Cite
|
Sign up to set email alerts
|

Transhepatic cholangiography in patients with suspected biliary disease and nondilated intrahepatic bile ducts

Abstract: Transhepatic cholangiography (THC) was performed in 107 patients who had nondilated intrahepatic bile ducts on computed tomography (CT) or ultrasound. The cholangiogram was diagnostic in 72 patients (67%). Thirty-one (43%) of the 72 diagnostic studies were abnormal and showed poor emptying, stones, or strictures. Twenty-three (21%) complications occurred, including two deaths. Sixteen patients experienced acute pain, requiring additional narcotics. There was one case of peritonitis and pancreatitis, and two of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 17 publications
0
45
0
1
Order By: Relevance
“…In the past, patients with altered anatomy and a failed conventional ERCP have been referred for surgical or percutaneous interventions which are associated with greater morbidity and cost compared to ERCP [12]. Percutaneous transhepatic cholangiography (PTC) has several technical limitations, including patients with ascites and coagulopathy and those with non-dilated biliary ducts.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, patients with altered anatomy and a failed conventional ERCP have been referred for surgical or percutaneous interventions which are associated with greater morbidity and cost compared to ERCP [12]. Percutaneous transhepatic cholangiography (PTC) has several technical limitations, including patients with ascites and coagulopathy and those with non-dilated biliary ducts.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, more invasive procedures, such as percutaneous interventions and open surgery, have been selected as primary treatments for biliary disease in these patients ( 4 ). However, the application of percutaneous transhepatic biliary drainage is limited by factors such as anticoagulant use and the presence of intrahepatic biliary dilatation or ascites ( 5 ), and open surgery is highly invasive.…”
Section: Introductionmentioning
confidence: 99%
“…The endoscopic approach via endoscopic retrograde cholangiopancreatography (ERCP) is the first choice [6,13,14,15,16]. When ERCP is not successful or not feasible, percutaneous transhepatic biliary drainage (PTBD) becomes an alternative.…”
Section: Introductionmentioning
confidence: 99%
“…The first clinical studies on accessing nondilated bile ducts for percutaneous transhepatic cholangiography (PTC) reported a 25% technical success rate and a 21% complication rate [15,18]. More recent small series have shown that PTC and subsequent drainage for a variety of indications can be feasible in patients with nondilated bile ducts as well; the technical success rates were similar to those in patients with dilated bile ducts (91-100%) [17,19,20,21,22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%